Effect of fermented oyster (Crassostrea gigas) extracts and regular walking on muscle strength and mass in older adults with relatively low muscle mass: A randomized controlled trial - Lee, Ye Li; Lee, Sang Yeoup (Frontiers in Nutrition, 2022)
IIntroduction: Oysters possess an excellent nutritional profile containing γ-aminobutyric acid (GABA). Previous data suggest that GABA is a potent bioactive compound for improving muscle health. Lactic acid fermentation is thought to increase GABA content. However, the effect of oral supplementation of fermented oyster extracts (FO) on human muscle strength and mass is unclear. Therefore, we tested the effects and safety of consumption of FO combined with regular walking for 12 weeks on muscle strength and mass in older adults with relatively low muscle mass. Materials and Methods: A randomized controlled trial was conducted on 54 adults between 50 and 78 years of age. Participants were randomized to receive either placebo or 1,200 mg FO daily for 12 weeks. By fermentation with Lactobacillus brevis BJ20, FO was prepared from Crassostrea gigas. At baseline and at 12 weeks after treatment, the following parameters of the participants were examined: knee strengths, handgrip strengths, body composition, blood tests, and 24-hour dietary recall. All participants were required to walk for 30–60 min/day for >3 days/week during the trial period. Physical activity was assessed using an exercise log during the study. Results: Of the 54 participants, 49 completed the trial without reporting adverse effects. FO supplementation over 12 weeks did not cause any increase in knee or grip strength compared to the control group. Also, no differences were observed in the muscle mass, growth hormone, muscle biomarkers, anti-inflammatory markers, and antioxidative markers between the two groups. None of the participants experienced adverse events. Application of FO was well tolerated, and no notable adverse effect was reported in both groups. Discussion: FO supplementation with regular walking did not improve remarkably muscle function compared to regular walking alone in adults with relatively low muscle mass.